Revisiting the need to regulate foreign portfolio investor in the Indonesian stock market - Ulya Yasmine Prisandani; Felix Pratama Tjipto (Faculty of Law, University of Muhammadiyah Malang, 2021)
This research aims to reintroduce the issue of foreign portfolio investment in Indonesia by way of presenting an analysis on the prevailing Indonesian laws and regulations, comparative analysis with well-established jurisdictions, as well as an evaluation on the need for regulating foreign portfolio investment in Indonesia. The methods used in this research combine normative and empirical methods where a review is conducted on the laws and regulations in Indonesia as well as in South Korea and India as comparative jurisdictions, in addition to an interview conducted with the Indonesian Stock Exchange. The research found that Indonesia does not have a separate, comprehensive set of regulations on foreign portfolio investments yet whereby inferences need to be made from the prevailing laws and regulations that are general in nature. After the comparative overview and analysis, there appears to be a need for separate regulation for foreign portfolio investments in Indonesia, either by way of enacting a completely new set of laws and regulations or alternatively, by way of creating implementing regulations to support the prevailing laws.